(دراسة فكرة ثعلب عن قاعدة النحوي (ممثِّلُ أهل النحو من المذهب الكوفي: Study of the Idea of Tsa'lab on the Rule of Grammar (Representative of Grammarians from the Kufi School) - Sirfi Fatoni, Ahmad (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2025)
Abstract This research reveals Tsa'lab, a world-famous Kufi grammarian, his idea and the most important representative of the Kufi school. Such research is still rare in Indonesia, and this research is essential and prestigious in revealing a person who has a great contribution to building the grammar base. The type of this research is qualitative research using descriptive and critical analysis. The discoveries are as follows: (1) Tsa'lab believed that the alif in the dual noun is a substitute for the two dhammahs in Zayd and Zayd, and that the waw is a substitute for the three dhammahs in Zayd, Zayd and Zayd, and this is a unique idea of ​​Tsa’lab as a representative of the Kufi school; (2) Tsa'lab added the verbs نشب and قام to the sisters of كادَ; (3) Al-Kisa'i and Al-Farra' believed that the function of inna can be invalidated if inna’s ism is far from it, and we see that Tsa'lab sing the words of Badui people:فليت ابن جوَّابٍ من الناس حظُّنا * وأنَّ لنا في النار بعدُ خلودُ.” He says after it: "وأنَّ لنا في النار بعدُ خلودُ" inna’s ism رُفِعَ على الاستئنافِ ; (4) Tsa’lab chooses the opinion of Basrah school in the matter "إِذَنْ" that it is permissible to cancel عمل إذنْ and رفعُ المضارع after it with the meeting of the conditions requiring the النصب, such as: "إِذنْ تُفْلِحُ" in response to someone who said: "سَأَجتهِدُ"; (5) Tsa’lab’s take sides towards the Kufi school of thought is more relative to his take sides towards the Basrah school of thought, because he is from the grammarians of Kufa; (6) Tsa’lab relied greatly on السماع and الرواية and knowledge of the anomalous and rare parts of the language and its derivations on the tongues of the Arabs and the strange parts of the speech of the Arabs in building his idea about nahwu.